A deep face-mask detection model using DenseNet169 and image processing techniques - Bhowmik, Durjoy; Abdullah, Mohd.Rahat Bin; Islam, Mohammed Tanvirul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.